2009
DOI: 10.1093/aob/mcp184
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ABA signalling genes and ABI5 protein levels in imbibed Sorghum bicolor caryopses with contrasting dormancy and at different developmental stages

Abstract: Several genes involved in ABA signalling are regulated differently in imbibed caryopses from two sorghum lines with contrasting pre-harvest sprouting response before - but not after - physiological maturity. A role for ABI5 in the expression of dormancy during grain development is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 33 publications
(42 reference statements)
3
48
0
Order By: Relevance
“…The role of ABI5 in dormancy induction is discussed (Finkelstein et al 2008) mostly because of the lack of such research concerning Arabidopsis seeds (Dekkers et al 2016). Research with orthologues, however, has confirmed that ABI5 homologues are more highly expressed in dormant sorghum cultivars (Rodríguez et al 2009). Despite this, Finkelstein et al (2008) concluded that further studies were required to confirm the role of ABI5 in seed dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…The role of ABI5 in dormancy induction is discussed (Finkelstein et al 2008) mostly because of the lack of such research concerning Arabidopsis seeds (Dekkers et al 2016). Research with orthologues, however, has confirmed that ABI5 homologues are more highly expressed in dormant sorghum cultivars (Rodríguez et al 2009). Despite this, Finkelstein et al (2008) concluded that further studies were required to confirm the role of ABI5 in seed dormancy.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, new mapping studies are needed to narrow these QTL and carry out future fine mapping analysis to identify individual genes. Of particular interest was the co-localisation of genes SbABI3/VP1 and SbGA20ox3 within qGI-3, taking into account that ABA sensitivity and GA metabolism are the most relevant physiological components to explain differences in seed dormancy behaviour for the parental lines used in this work (Steinbach et al 1995;Gualano et al 2007;Rodríguez et al 2009Rodríguez et al , 2012. On the other hand, the detected QTL do not colocalise with known wheat PHS QTL and seem to result from different genes.…”
Section: Discussionmentioning
confidence: 99%
“…Other features, such as the panicle architecture, glumes or glumellae presence and seed tannin content, which could actually affect the relationship between dormancy and PHS susceptibility, have been shown not to be involved in IS9530/RedlandB2 PHS behaviour (Steinbach et al 1995). Premature release from dormancy in RedlandB2 grains has been ascribed to a reduced sensitivity of their embryos to the germination inhibitory action of abscisic acid (ABA) and an abnormal accumulation of active gibberellins (GAs) (Steinbach et al 1995(Steinbach et al , 1997Rodríguez et al 2009Rodríguez et al , 2012. Both processes (faulty ABA sensitivity and GA inactivation) have been found to be differentially regulated in this line at the transcriptional level of genes involved in ABA signalling and GA catabolism (Rodríguez et al 2009(Rodríguez et al , 2012.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of methyl jasmonate reduces dormancy and ABA content in imbibed wheat grains and this is mediated via a reduction in TaNCED1 and an increase in TaABA8 0 OH-1 expression (Jacobsen et al, 2013). While maintenance of high ABA concentrations after imbibition is required for the expression of dormancy in the barley grain, this is not the case in some wheat and sorghum genotypes (Rodríguez et al, 2009;. In grain sorghum (S. bicolor), coat-imposed dormancy in two inbred lines with contrasting dormancy is not related to ABA content, which decreases similarly upon grain imbibition (Gualano et al, 2007;Rodríguez et al, 2009).…”
Section: Hormones In the Expression Of Dormancy In The Imbibed Grainmentioning
confidence: 99%